2022
DOI: 10.3389/fendo.2022.979054
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size is an independent negative prognostic factor for event free survival in children with differentiated thyroid cancer

Abstract: BackgroundThe incidence of pediatric differentiated thyroid carcinoma (DTC) is increasing. Despite the advanced disease at presentation, the overall prognosis of DTC in children is excellent. The aim of this study is to investigate the risk stratifying factors for event free survival (EFS) of pediatric DTC from Middle Eastern ethnicity.MethodsEighty-eight patients aged ≤18 years with diagnosis of primary DTC were retrospectively analyzed. Cox proportional hazards model were used to calculate Hazard Ratios (HR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In a cohort of 88 pediatric DTCs with mean follow‐up of 8.4 years, Parvathareddy et al. did not observe any significant difference in the long‐term event‐free survival between the less than or equal to 15 years and more than 15 years age groups 19 . Similarly, Cistaro et al.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a cohort of 88 pediatric DTCs with mean follow‐up of 8.4 years, Parvathareddy et al. did not observe any significant difference in the long‐term event‐free survival between the less than or equal to 15 years and more than 15 years age groups 19 . Similarly, Cistaro et al.…”
Section: Discussionmentioning
confidence: 90%
“…In a cohort of 88 pediatric DTCs with mean follow-up of 8.4 years, Parvathareddy et al did not observe any significant difference in the long-term event-free survival between the less than or equal to 15 years and more than 15 years age groups. 19 Similarly, Cistaro et al evaluated pediatric DTC patients over a median follow-up of approximately 11 years, and did not find age as a continuous variable to be predictive of long-term disease-free status.…”
Section: Discussionmentioning
confidence: 99%
“…[1,5,7,14,17] Our study also found a similar result that younger age was associated with higher TI-RADS, higher pN stage, higher ATA pediatric risk, and multifocality (all P < .05). Children with DTC often need a wider range of cervical lymph node dissection, and more iodine-131 radiotherapy Parvathareddy SK [37] (2022) (P < .05). However, there was no significant difference between the 2 groups in pT/pM stage and bilaterality in our study, possibly because of the limited sample size.…”
Section: Comparison Of Clinicopathological Features and Treatments Of...mentioning
confidence: 99%
“…According to the eighth edition of the AJCC-TNM staging system, ETE for thyroid carcinomas was divided into minimal and gross ETE. Minimal ETE is defined as the tumor invasion of the perithyroid soft tissue, while gross ETE refers to invasion into strap muscles and major neck structures (subcutaneous soft tissue, larynx, trachea, esophagus, recurrent laryngeal nerve, the prevertebral fascia, or it encases the carotid artery or mediastinal vessels) [9][10][11]. Surgery is the most effective means of routinely treating PTC.…”
Section: Introductionmentioning
confidence: 99%